Exploring roots, recognizing differences : promoting inter-religious communication in Malaysia. - Ahmad, Abd Mua'ti @ Zamri (Wiley-Blackwell, 2010)
Malaysia is a unique country with a blend of multi-racial and multi-religious population. The people of Malaysia live harmoniously despite major differences in their beliefs and faith. Although the Malaysian constitution stated that Islam is an official religion of the country, the people are guaranteed freedom to practice any religion. However, with the escalation of inter-religious conflicts elsewhere in the world, especially post-9/11 tragedy, Malaysians had to embark on promoting inter-religious communication in order to avoid misunderstanding. Even so, are Malaysians ready to share such understandings? This paper discusses the views of Malaysians on their willingness to explore and recognize the faith of their fellow countrymen.